Personalized Medicine: Evaluating The Role of Genomic Data in Tailoring Cancer Treatments. A Bibliometric Perspective - Virk, Razia; Ririe, Avrina Kartika; Lashari, U.G.; Yousif Mohamed, Mazar Mohamed; Rafique, Tariq; Iqbal, Hrishik; Nazir, Ayesha (Journal of Neonatal Surgery, 2025)
Personalized medicine, a paradigm shift in cancer treatment, leverages genomic data to tailor therapies to individual patient profiles. This bibliometric analysis focuses on tracing the development of the literature on the use of genomic information in decision-making for developing individualized cancer treatments. In general, for the study, we compared the Earliest Indexing and Latest Indexing of English-language articles and reviews that were published between January 1, 2000, and June 30, 2024, using the Web of Science Core Collection. Among the total 1,234 researched articles, number of articles found were 890 of which 344 were reviews. This research output level has gradually risen with the highest number of papers at 189 in the year 2023. Pertaining to the year 2019, the United States has the most numerous journal articles with a total of 320 articles and the highest citation of 25, 489. In addition to this, many contributions have come from European and Asian institutions particularly from Germany, China and Japan. Some of the key researchers involved are basically Vogelstein/Johns Hopkins University, Mantovani/University of Milan and Eric Lander/ Broad Institute. Regarding the first variable, the descriptive results indicated that Johns Hopkins University has the highest publication output among the enumerated research institutions while articles published in Broad Institute were cited most frequently. Some of the journals of high standing in this area are Cancer Research; Nature Reviews Clinical Oncology, Journal of Clinical Oncology. Finally, it is incumbent upon the hail and farewell to state that several phrases are now integral to the domains of investigation: precision medicine; targeted therapy; genomic profiling; and tumor heterogeneity. This work demonstrates that genomic data play an essential part in optimizing cancer therapies, reinforcing the call for integrative collaboration and approaches worldwide for further improvement of personalized cancer management.